Sovereignty of a nation in the parliamentary system of Lithuania: Problems and proposals - Arlauskas, Saulius (Creativity Studies, 2010)
The aim of the article is to show in what way it is possible to guarantee the proper representation of human interests in the parliamentary form of government. To quote ideas of Mykolas Romeris concerning relationships between sovereign and State powers, it is stated that a special function of safeguarding of constitutionality as an expression of the Sovereign’s will ought to be provided in the Constitution of Parliamentary Republic. In the article, it is demonstrated that such function is implemented in the Constitutions of France and Germany by granting a President to guarantee a proper work of parliamentary system (the function of political and legal reserve). It is also shown that in Lithuania, which is considered to be a Parliamentary Republic, the President does not perform a function of political and legal reserve and does not have appropriate authorizations. The author of the article proposes to follow the standards of Constitutions of France and Germany and to reconsider the competences between the institutions of the Seimas and the President. Tautos suverenitetas parlamentinėje Lietuvos sistemoje: problemos ir pasiūlymai Santrauka. Straipsnyje siekiama parodyti, kaip parlamentinė valdymo forma gali užtikrinti deramą žmonių interesų atstovavimą. Remiantis Mykolo Romerio idėjomis apie suvereno ir valdžios santykį teigiama, kad parlamentinės valstybės Konstitucijoje privalo būti numatyta speciali konstitucingumo apsaugos funkcija kaip suvereno valios išraiška. Parodoma, kad tokia funkcija numatyta Prancūzijos ir Vokietijos Konstitucijose, suteikiant Prezidentui funkciją užtikrinti deramą parlamentinės sistemos veikimą (politinio ir teisinio rezervo funkcija). Atskleidžiama, kad Lietuvoje, kuri taip pat yra laikoma parlamentine respublika, Prezidentas politinio ir teisinio rezervo funkcijos neatlieka ir atitinkamų įgaliojimų neturi. Straipsnyje siūloma pasekti Prancūzijos ar Vokietijos Konstitucijų pavyzdžiu ir peržiūrėti Seimo bei Prezidento kompetencijas. Reikšminiai žodžiai: Konstitucija, Lietuva, suverenitetas, valstybės valdžios padalijimas. First published online: 10 Feb 2011